2023
DOI: 10.3389/fmed.2022.1065045
|View full text |Cite
|
Sign up to set email alerts
|

Vietnam Association of Gastroenterology (VNAGE) consensus on the management of Helicobacter pylori infection

Abstract: Helicobacter pylori (H. pylori) infection is prevalent and has a rapidly increasing antibiotic resistance rate in Vietnam. Reinfection is quite common, and gastric carcinoma remains one of the most common malignancies, which is not uncommon to develop after successful eradication. The purpose of this consensus is to provide updated recommendations on the management of H. pylori infection in the country. The consensus panel consisted of 32 experts from 14 major universities and institutions in Vietnam who were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
4

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 79 publications
0
12
0
4
Order By: Relevance
“…30,58 Furthermore, the integration of LEV as an empiric alternative first-line treatment for H. pylori in Vietnamese adults has also contributed to the emergence and rapid increase of LEV resistance. 48 Importantly, self-medication is also very common in Vietnam. 31 These factors might contribute to the high level of LEV resistance in children.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…30,58 Furthermore, the integration of LEV as an empiric alternative first-line treatment for H. pylori in Vietnamese adults has also contributed to the emergence and rapid increase of LEV resistance. 48 Importantly, self-medication is also very common in Vietnam. 31 These factors might contribute to the high level of LEV resistance in children.…”
Section: Discussionmentioning
confidence: 99%
“…The TET-resistant strains in children are probably transmitted from adults, where resistance rates ranged from 5.8% 33 to 10.9%, 66 since TET is commonly used as a first-line regimen in adults. 48 In Vietnam, most studies have reported higher secondary resistance compared with primary resistance. 28,29,44 Our results showed similar trends for CLA, LEV, and TET, but without statistically significant differences.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations